Penerapan Customer Relationship Management (CRM) Dalam Sistem Informasi Penjualan Kosmetik Berbasis Web - Anggara, Nadia Ayu Agustri; Hutahaean, Jeperson; Iqbal, Muhammad (Forum Kerjasama Pendidikan Tinggi, 2022)
CRM is a marketing strategy to create and maintain a good relationship with customer and decrease the possibility customer move away to other competitors. This research present the analysis of web-based CRM development in Marketing Information System at Toko ZU MS GLOW SUMUT STOCKIST. The result is an CRM web-based system which can manage customer data, product promotion, product sales data and managing of customer service that used to save customer question and complain to create good relationship with customer. This application, Toko ZU MS GLOW SUMUT STOCKIST is expected to mantain good relationship with customer or get new customer, which eventually bring benefits to the company. With this method, results can be obtained in the form of the realization of a Customer Relationship Management Application to simplify, accelerate and optimize the quality of customer service